Responsible waste management : safely shipping conditioned nuclear waste from Europe to Japan (International Nuclear Services CheshireGB, 2011)
Reports on the processing of radioactive waste to a form safe for tranportation and storage and its transhipment from Europe to Japan.
Keywords: NUCLEAR INDUSTRY